La Première Guerre mondiale et les jeux vidéo - Antoine Maillard (Conserveries Mémorielles)
Since the beginning of the Centenary of the First World War, we see a lot of production around this event: movies, books, documentaries…The Great War, which was the least represented in video games, begin to be used more and more by developers in their productions: Valiant Hearts: The Great War in 2014, Verdun 1914-1918 in 2015, Battlefield 1 in 2016… To create those worlds based on history, developers must learn some historical knowledge about those eras. But which influences are they using? Did the developers read some academic studies? Other historical knowledge provider? Or, does they base their work on their interpretation of the sources using their own knowledge? Also, the Great War is a difficult era to represent in media, seem as a “sad war”, without real goal or justifications. Developers must take those specificities into account to create their game, their speech about this conflict and their gameplay. This study will focus on Battlefield 1, release the 21 October 2016 by DICE. The representation of the First World War in this game was analyse several times by developers, media and historians.